Strengthening Student Character Education at the Tri Integrated Nature School of Education Center - Muhammad Sholeh; Syahrial Syahrial; Supian Supian; Muhammad Sofwan (GHAITSA : Islamic Education Journal, 2026)
This study aims to analyze the strengthening of character education for students in nature schools based on the philosophy of Ki Hajar Dewantara. Using a descriptive qualitative method, the study was conducted at two nature schools, namely Sekolah Alam Muaro Bungo (SAMO) and Madrasah Alam Insan Rabbani, involving 12 participants consisting of school principals, teachers, students, and parents. Data collection was conducted through observation, interviews, and documentation. The results of the study indicate that the strengthening of character education in nature schools is carried out through three main programs: exemplary leadership grounded in the philosophy of Ing Ngarsa Sung Tuladha, habit formation based on Ing Madya Mangun Karsa, and meaningful interpretation rooted in Tut Wuri Handayani. These three programs are implemented in an integrated manner through collaboration between the school and parents within the framework of the Tri Pusat Pendidikan. These findings indicate that the nature school approach, which holistically integrates Ki Hajar Dewantara’s philosophy, is capable of shaping students’ character to be strong, consistent, and grounded in local wisdom.